Sakkayaphāp kh̨̄ong phūsūng ʻāyu nai kānthamngān ph̄ưa sangkhom - Kr̄œksak Bunyānuphong (Khrōngkān Charāphāpsưksā, Sathāban Wičhai Sangkhom, Mahāwitthayālai Chīang Mai, 1991)
Study on ability and willingness of aged to work for social welfare in Thailand.